New Language Acquisition for Refugees: A Key to Effective Transitioning - McLoughlin, Shirley Wade ("Intercultural Dialogues" Transactions, 2023)
Acquiring a second language has economic, educational, and social impact on individuals and families. When considering the rapid expansion of individuals identifying as refugees in today’s world, learning a new language takes on a new role; it is a critical component of refugees’ lives. For refugees, acquisition of the new language in their new country goes far beyond the aforementioned benefits; it is a crucial part of positive transitioning to their resettlement in a new country. While there are many components for refugees’ successful integration into a new society, learning and using a second language is interwoven into many of these components as a means of attaining effective resettlement. Using Ager and Strang’s (2008) domains for refugee integration, this article highlights the role language acquisition plays in some key domains, especially in acquiring employment, in educational opportunities, in healthcare, in development of social connections, and, if desired, in citizenship. In addition to examining these areas, this paper explores the impact of strong second language development and factors that impact the learning of the new language, including those occurring prior to coming to the refugees’ new country, experiences occurring during their flight from their native homes, and in their experiences in their native homes prior to becoming refugees.